Design and Construction Of The Ecostove Product “Jolseuneu” As A Form Of Utilization of Waste Cooking Oil in Cibaduyut Kidul Village - Effendi, Muhammad Zidan; Sutana, Deni; Maulin, Adysti; Maharani, Novi Suci; Aditya, Syifa; Elora, Devi (Jurnal Pengabdian Tri Bhakti, 2025)
This study aims to determine the design and implementation of the EcoStove "JOLseuneu" product as a form of utilization of household waste cooking oil (jelantah) in the Cibaduyut Kidul sub-district, Bojongloa Kidul district, Bandung City. This research is based on fieldwork because it involves tools and materials as well as socialization with the community. The results obtained indicate that the EcoStove "JOLseuneu" product is very easy to apply as an alternative stove and can provide a concrete solution for the utilization and management of used cooking oil waste, as well as a form of environmentally friendly fuel savings (biogas/biomass).